Estabelecendo as Diferenças entre os Termos Registro e Gênero - Santos, Valeria Branco Moreira Pinto dos (The ESPecialist, 2012)
This paper, adapted from an MA thesis (Santos, 1996), discusses theoretical concepts on the definition and usage of both terminologies: register (Halliday, 1978; 1989; 1994) and genre (Swales, 1990). It is an attempt to establish theoretical differences in order to make it easier for the researchers and the teachers to distinguish between both concepts. The bibliographical survey carried out for this article does not bring about clearly-established definitions, but points towards the importance and relevance of both concepts either for academic studies or for pedagogical practice.